Nurses’ Behaviors, Perceptions and Diagnoses in the Diagnosing Phase of the Nursing Process within the Scope of a Case Study: A Mixed Type Study - Arzu Akman Yılmaz; Ahu Çırlak (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: The nursing process is a systematic, dynamic problem-solving process that expresses the way of thinking and acting that nurses use in performing their practices.Aim: It aims to examine nurses' perceptions of nursing diagnoses, their behaviors regarding the diagnosis phase, and their ability to identify appropriate diagnoses within the scope of a case study.Method: 103 nurses working in a private hospital in Ankara participated in the study. Both qualitative and quantitative research methods were used. Quantitative data were obtained with questionnaires, the Perceptions of Nursing Diagnosis Survey, and reports created by the nurses. Qualitative data were obtained from the observation notes kept by observing the behaviors of the nurses regarding the diagnosis.Results: Approximately half of the nurses had difficulties in data collection, diagnosis, and planning phases. Nurses had less difficulty obtaining a health history from the patient and determining subjective data after the case analysis. There was no significant difference between pre-test and post-test results regarding the problems experienced during the diagnosis phase, but their perceptions of nursing diagnoses changed positively. In the planning phase, nurses' post-test results increased significantly. As a result of the content analysis, the behaviors related to the diagnosis phase were discussed under three main themes: “data collection”, “using reference book”, and “diagnosing”.Conclusions: The case study contributed to the nurses' experience of how to deal with the diagnosis of the individuals and raising awareness of the problems they experienced in this phase.